Odpowiedzi

2009-12-06T20:02:09+01:00
A) 2x - y = -7
4(x+1) + 2y = 18

2x - y = -7 /*(-2)
4x + 2y = 14

-4x + 2y = 14
4x + 2y = 14

4y = 28
y=7
2x - 7 = -7
2x = 0
x = 0


b) 6x - 2y = 10 /* (-2)
3x - 4y = 32

-12x + 4y = -20
3x - 4y = 32

-9x = 12
x = -4/3
-8 - 2y = 10
-2y = 18
y = -9
  • Anko
  • Rozwiązujący
2009-12-06T20:20:53+01:00
A) razy--> *
|2x-y=7 /*2
|4x +4 +2y=18

|4x-2y=14
|4x+2y=14
--------------------------
8x=28 /:8
x=3,5

2*3,5-y=7
-y=7-7

y=7


b)
|6x-2y=10 /:(-2)
|3x+4(1-y)=36

|-3x+y=-5
|3x+4-4y=36

|-3x+y=-5
|3x-4y=32
---------------------
-3y=27 /:(-3)
y=-9

3x-4*(-9)=32
3x=32-36
3x=-4
x=-1,(3)

2 4 2